Comparison between diagnosis and treatment of community-acquired pneumonia in children in various medical centres across Europe with the United States, United Kingdom and the World Health Organization guidelines. Issue 1 (December 2016) - Usonis, Vytautas; Ivaskevicius, Rimvydas; Diez-Domingo, Javier; Esposito, Susanna; Falup-Pecurariu, Oana; Finn, Adam; Rodrigues, Fernanda; Spoulou, Vana; Syrogiannopoulos, George; Greenberg, David
Abstract Background The aim of this study was to review the current status and usage of guidelines in the diagnosis and treatment of community-acquired pneumonia (CAP) in European countries and to compare to established guidelines in the United States (US), United Kingdom (UK), and the World Health Organization (WHO). Methods A questionnaire was developed and distributed by the Community-Acquired Pneumonia Paediatric Research Initiative (CAP-PRI) working group and distributed to medical centres across Europe. Results Out of 19 European centres, 6 (31.6 %) used WHO guidelines (3 in combination with other guidelines), 5 (26.3 %) used national guidelines, and 5 (26.3 %) used local guidelines. Chest radiograph and complete blood count were the most common diagnostic examinations, while evaluation of clinical symptoms and laboratory tests varied significantly. Tachypnoea and chest recession were considered criteria for diagnosis in all three guidelines. In US and UK guidelines blood cultures, atypical bacterial and viral detection tests were recommended. In European centres in outpatient settings, amoxicillin was used in 16 (84 %) centers, clarithromycin in 9 (37 %) centers and azithromycin in 7 (47 %) centers, whereas in hospital settings antibiotic treatment varied widely. Amoxicillin is recommended as the first drug of choice for outpatient treatment in all guidelines. Conclusions Although local variations in clinical criteria, laboratory tests, and antibiotic resistance rates may necessitate some differences in standard empirical antibiotic regimens, there is considerable scope for standardisation across European centres for the diagnosis and treatment of CAP.